Food Crisis In Africa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRACT in most cases the chronic food crisis in Africa has been ascribed to natural calamities such as drought. it is the primary objective of this paper to examine the political, economic and social factors which have and continue to militate against food production in Africa The paper while accepting that natural disasters have contributed to the food crisis makes it vividly clear that the policies of development by various, African governments have contributed most greatly to Africa's food predicament